Exploring Leadership Development Through Community‐Based Experiences. Issue 4 (April 2017) - McKim, Aaron J.; Velez, Jonathan J.; Stewart, Josh; Strawn, Kellie
Abstract : The current study explored community‐based experiences as a method for leadership development within a College of Agricultural Sciences leadership development program at Oregon State University. The value of community‐based experiences was gauged by evidence of student progression through the experiential learning cycle. Student reflections indicated community‐based involvement provided a concrete experience in leadership, a foundational element to experiential learning. Additionally, evidence emerged indicating students gained new insights through reflecting on community‐based experiences, an additional element of the experiential learning cycle. Furthermore, experiences and reflections encouraged students to identify new conceptualizations for leadership moving forward, an important step to experiential learning. Finally, after completing the community‐based experience, students were poised to continue leadership in new roles, at different locations, with improved approaches. Considerations for the application of community‐based experiences in leadership education are discussed.